2021
DOI: 10.3390/atmos12070893
|View full text |Cite
|
Sign up to set email alerts
|

Particle Number Emissions of Gasoline, Compressed Natural Gas (CNG) and Liquefied Petroleum Gas (LPG) Fueled Vehicles at Different Ambient Temperatures

Abstract: Compressed natural gas (CNG) and liquefied petroleum gas (LPG) are included in the group of promoted transport fuel alternatives for traditional fossil fuels in Europe. Both CNG and LPG fueled vehicles are believed to have low particle number and mass emissions. Here, we studied the solid particle number (SPN) emissions >4 nm, >10 nm and >23 nm of bi-fuel vehicles applying CNG, LPG and gasoline fuels in laboratory at 23 °C and sub-zero (−7 °C) ambient temperature conditions. The SPN23 emissions in CNG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…The present results are in agreement with other studies that reported CNG vehicles as high suppressors of PN emission [26,27]. However, these results only included particles emitted in the range of 23-1000 nm.…”
Section: Cng Busessupporting
confidence: 93%
See 2 more Smart Citations
“…The present results are in agreement with other studies that reported CNG vehicles as high suppressors of PN emission [26,27]. However, these results only included particles emitted in the range of 23-1000 nm.…”
Section: Cng Busessupporting
confidence: 93%
“…However, these results only included particles emitted in the range of 23-1000 nm. Several recent studies have shown that CNG and liquified natural gas (LNG) vehicles have particularly high PN emissions in the sub-23 nm range [24,[27][28][29]. On-road tests of PN emission factors, with PNC measurements starting at a particle size of 2.5 to 5 nm, revealed that a CNG truck had higher emission than three diesel-fueled vehicles with DPF certified to the same emission standards [30].…”
Section: Cng Busesmentioning
confidence: 99%
See 1 more Smart Citation
“…SPN 23 and SPN 10 emissions were calculated using the total CVS flow and the Particle Correction Reduction Factor (PCRF) (of 30 nm, 50 nm, and 100 nm) according to the Regulation [3]. SPN 10 was corrected for additional particle losses due to diffusion at the sampling point, as it was sampling from the secondary outlet of the instrument and not from the internal position as the 23 nm counter [12]. Specifically, for the sub-23 nm particles, SPN 10 -SPN 23 , we calculated 20% more losses than those considered in the PCRF and we corrected accordingly the results.…”
Section: Evaluation Methodologymentioning
confidence: 99%
“…By utilizing CNG to power fuel-cell electric vehicles (e.g., cars or trucks) or as a feedstock for synthetic aviation and marine fuels, the low-carbon economy can replace the need for fossil fuels such as fossil-based gasoline and diesel. Recently, interest in CNG-based vehicles has grown in the US and Indian markets because they are more affordable, less combustible and deliver more energy [76,77].…”
Section: Hydrogen-enriched Methanementioning
confidence: 99%